An Early Presentation of Tricuspid Valve Rupture in a Trauma Patient With Congenital Heart Disease - Justus Boever; Rishi Batra; Hason Khan; Zachary M. Bauman (Case Reports in Surgery)
Tricuspid valve regurgitation/rupture is a rare complication of trauma, with only around 150 cases reported in the literature, though this prevalence may be underestimated due to subtle clinical manifestations. The tricuspid valve is the most frequently affected heart valve following blunt chest trauma due to its anterior anatomical position between the sternum and the vertebrae. The diagnosis of tricuspid regurgitation is often delayed in the traumatic setting due to the subtlety of clinical manifestations. Many trauma patients also present with distracting injuries. The subsequent treatment delay can result in development of irreversible dilatation of right-sided heart chambers, making it imperative to have a high index of suspicion for tricuspid regurgitation as a cause of acute hemodynamic instability in the setting of blunt trauma to the chest. In this report, we present a unique case of traumatic tricuspid valve regurgitation in a patient with a history of congenital atrial septal defect (ASD)/partial anomalous pulmonary venous return (PAPVR).